2017
DOI: 10.3201/eid2301.160608
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Anthrax Immune Globulin Intravenous with Antimicrobial Treatment in Injection Drug Users, Scotland, 2009–2010

Abstract: Differences between recipients and nonrecipients and the small number of higher risk patients confounded assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…anthracis soft-tissue infection during the 2009 to 2010 outbreak in Scotland related to the use of contaminated heroin. [ 9 ] Notably, review of 43 patients from that outbreak including all AIG recipients, showed that mortality in this uncontrolled experience did not differ comparing recipients and non-recipients. However, comparisons between these recipients and non-recipients are difficult to make.…”
Section: Introductionmentioning
confidence: 90%
“…anthracis soft-tissue infection during the 2009 to 2010 outbreak in Scotland related to the use of contaminated heroin. [ 9 ] Notably, review of 43 patients from that outbreak including all AIG recipients, showed that mortality in this uncontrolled experience did not differ comparing recipients and non-recipients. However, comparisons between these recipients and non-recipients are difficult to make.…”
Section: Introductionmentioning
confidence: 90%
“…However, a meta-analysis of 9 such studies did not show significant results. 16 It is well documented that a timely and appropriate antibiotic therapy leads to dramatic recovery. Bacillus anthracis from naturally occurring cases is invariably penicillin sensitive.…”
Section: Treatmentmentioning
confidence: 99%
“…The medical countermeasures against a bioterrorist occurrence or a natural emergence are frequently overlapping, as exemplified by the use of polyclonal serum during an outbreak of anthrax in drug users, or the Ebola vaccine in the outbreaks in Africa this decade. 8,9 Nationally and transnationally, interfacing and strengthening the research, development, and implementation of these counter-measures is clearly beneficial for global health and security. Building efficient communications is a big part of the challenge.…”
Section: The Threat Of Bioterrorismmentioning
confidence: 99%